Colocalization of cortactin and PH domain of BCR in HEK293T cells and its potential role in cell signaling - Gurianov, D.S.; Antonenko, S.V.; Telegeev, G.D. (Вiopolymers and Cell, 2016)
Chromosomal translocation t(9;22)(q34;q11) leads to the generation of different types of the BCR-ABL fusion protein and cause different types of leukemias. The generated fusion proteins differ by the presence or absence of certain domains of BCR – C2, PH, and DH. The mass-spectrometric analysis identified 23 possible interaction partners of PH domain of BCR. Among them is cortactin (CTTN), which is a multidomain protein responsible for the actin branching during endocytosis. The activation of cortactin occurs after phosphorylation by SRC kinase. However, it is unknown whether ABL kinase can phosphorylate and activate CTTN in the same manner. Aim. To demonstrate whether CTTN and PH domain of BCR colocalize in HEK293T cells, to analyze possible phosphorylation sites for ABL kinase in the cortactin and to make a comparative prediction for SRC kinase. Methods. Cells HEK293T were transfected with the engineered pECFP-C3-CTTN and pmCitrine-C1-PH using a cationic polymer transfection and evaluated with fluorescent microscopy. Putative phosphorylation sites of CTTN by ABL and SRC kinases were predicted by GPS 2.1 software. Results. PH domain and CTTN were expressed in HEK293T cells and show specific cellular colocalization. The phoshorylation sites for Abl kinase (Y384, Y396, Y409, Y416, Y427, Y433, and Y449) were detected in the proline-rich region of CTTN and they match corresponded sites predicted for SRC kinase. Conclusions. We have shown that CTTN has cytoplasmic localization and PH domain of BCR localized predominantly but not exclusively in the nucleus. Their partial colocalization occurs in specific dot-like perinuclear regions. A potential phosphorylation of CTTN by ABL may be one of the activation pathways during leukemogenesis. Хромосомна транслокація t(9;22)(q34;q11), яка призводить до утворення трьох різних форм химерного білка BCR-ABL, призводить до виникнення різних форм лейкемій. Вони відрізняються наявністю або відсутністю певних доменів – С2, РН і DH. Мас-спектрометричний аналіз ідентифікував 23 потенційних кандидати на взаємодію з доменом РН BCR. Серед них білок кортактин (CTTN) – мультидоменний білок, що бере участь в розгалуженні актину під час ендоцитозу. Активація корт актину здійснюється за рахунок фосфорилювання кіназою SRC. Однак невідомо, чи здатна ABL кіназа фосфорилювати та активувати CTTN схожим чином. Мета. Показати наявність або відсутність колокалізації між CTTN та доменом РН BCR, передбачити наявність сайтів фосфорилювання ABL кіназою в послідовності CTTN та порівняти ці сайти з передбаченими для SRC кінази. Методи. Клітини HEK293Т були трансфековані створеними конструкціями pECFP-C3-CTTN і pmCitrine-C1-PH за допомогою катіонних полімерів. Можливі сайти фосфорилювання CTTN ABL кіназою були ідентифіковані програмою GPS 2.1. Результати. Експресія домену РН і CTTN в клітинах 293Т показує їх специфічне внутрішньоклітинне розташування. Сайти фосфорилюваня ABL кіназою (Y384, Y396, Y409, Y416, Y427, Y433, and Y449) були знайдені в багатій на пролін ділянці CTTN і співпадають з сайтами, передбаченими для SRC кінази. Висновки. Показано, що CTTN має цитоплазматичну локалізацію, в домен РН локалізований переважно в ядрі, але присутній і в цитоплазмі. Вони частково колокалізовани в специфічних точкових навколоядерних ділянках. Можливе фосфорилювання CTTN ABL кіназою може бути одним із шляхів активації під час лейкемогенезу. Хромосомная транслокация t(9;22)(q34;q11), ведущая к образованию трех разных форм химерного белка BCR-ABL, приводит к возникновению разных типов лейкемий. Они отличаются наличием или отсутствием определенных доменов – С2, домены гомологии плекстрина (РН) и Dbl (DH). Масс-спектрометрический анализ идентифицировал 23 потенциальных кандидат на взаимодействие с РН доменом BCR. Среди них белок кортактин (CTTN) – мультидоменный белок, учавствующий в разветвлении актина во время ендоцитоза. киназой в последовательности CTTN, а также сравнить эти сайты с таковыми Активация кортактина осуществляется за счет его фосфорилирования киназой SRC. Однако не известно, может ли ABL киназа фосфорилировать кортактин и активировать его таким же образом. Цель. показать наличие или отсутствие колокализации между CTTN и доменом РН BCR, предсказать наличие сайтов фосфорилирования ABL для SRC киназы. Методы. Клетки HEK293Т были трансфецированы созданными конструкциями pECFP-C3-CTTN и pmCitrine-C1-PH с помощью катионных полимеров. Возможные сайты фосфорилирования CTTN ABL киназой были идентифицированы программой GPS 2.1. Результаты. Экспрессия домена РН и CTTN в клетках 293Т показывает их специфическое внутриклеточное расположение. Сайты фосфорилирования ABL киназой (Y384, Y396, Y409, Y416, Y427, Y433, and Y449) были найдены в богатом пролином участке CTTN и они совпадают с предсказанными сайтами фосфорилирования для SRC киназы. Выводы. Показано, что CTTN имеет цитоплазматическую локализацию, а домен РН локализирован преимущественно в ядре, но присутствует и в цитоплазме. Они частично колокализованы в специфических точкообразных околоядерных участках. Возможное фосфорилирование CTTN ABL киназой может быть одним из путей активации во время лейкемогенеза.